The price of football : understanding football club finance - Maguire, Kieran (Agenda Publishing, 2021)
This revised and updated second edition of the bestselling guide to understanding football club finance includes analysis of the most recent club accounts, as well as the impact of Covid-19 on the game's finances, the latest legal rulings on club affairs, and expanded coverage of ""creative accounting"".